Future Directions in Legal Education: Earth Jurisprudence and Rights of Nature - Katie O'Bryan (Bond Law Review)
Earth jurisprudence, and the associated Rights of Nature concept, are fields of law growing rapidly around the world, inviting us to rethink the way humans interact with the environment. As such, they have the potential to contribute to solving some of the most pressing environmental challenges of our time. This article argues that these concepts should be incorporated into the legal curriculum so that law graduates will be adequately equipped to help find enduring legal solutions to current environmental challenges. After providing some background and context, the article explores various ways in which these concepts could be taught, considers possible obstacles that may be encountered and outlines various options for adapting the legal curriculum. The article concludes that as well as providing students with knowledge of innovative legal pathways that are emerging in environmental law, there are also pedagogical benefits and positive learning outcomes that can be achieved. Further, institutional goals can also be addressed by incorporating Earth jurisprudence and Rights of Nature into the legal curriculum.